IMPLEMENTATION OF THE INDEPENDENT CURRICULUM TOWARDS IMPROVING THE CHARACTER OF DISCIPLINE AND HONESTNESS OF STUDENTS AT THE MUHAMMADIYAH DOLOPO MADIUN ELEMENTARY SCHOOL - Yuni Anjarwati; Sudarmadi; Nuraini (MUADDIB Jurnal Kependidikan dan Keislaman, 2022)
The independent curriculum is a new curriculum implemented after Covid-19. This curriculum is expected to be able to answer all educational problems that occur in Indonesia, including the problem of decreasing the character of discipline and honesty in students. One of the efforts made at Madrasah Ibtidaiyah Muhammadiyah Dolopo is to also use an independent curriculum which develops character, one of which is discipline and honesty. This research aims to determine (1) the implementation of the independent curriculum for improving the character of Discipline and Honesty of Students at the Muhammadiyah Dolopo Madiun Elementary School, (2) to determine the impact implementating of the independent curriculum on improving the character of Discipline and Honesty of Students at the Muhammadiyah Dolopo Madiun Elementary School, (3) to determine the inhibiting and supporting factors the independent curriculum in improving the character of Discipline and Honesty of Students at the Muhammadiyah Dolopo Madiun Elementary School. This research method uses a qualitative approach with a case study research type. Data collection techniques include interview techniques, observation and documentation. Data analysis techniques use data reduction techniques, data presentation, and drawing conclusions. The results of this research found that the implementation of the independent curriculum to improve students' disciplined and honest character has not gone compeletely well, it still requires adjustments from both students and teachers themselves. The implantation stage of learning to strengthen disciplined and honest character through the P5P2RA project, is integrated into intracuricullar, co-curicullar and extracuricullar activities. The impact implementating the independent curriculum on improving disciplined and honest character can increase students interest in talent. Factors that hinder the implementation of the independent curriculum in on improving the character of discipline and honesty in MI Muhammadiyah Dolopo Madiun students are the lack of teachers understanding of the independent curriculum in designing learning, the lack of adequate infrastructure that support archiving violations in the madrasa environment. Third, limited supervision from madrasa leader to techers and limited supervision from teacher to students in familiarizing students in the madrasa environment